IMPLEMENTATION OF MULTI-SYSTEM SILVICULTURE (MSS) TO IMPROVE PERFORMANCE OF PRODUCTION FOREST MANAGEMENT: A CASE STUDY OF PT. SARPATIM, CENTRAL KALIMANTAN - Suryanto, Suryanto; Susilo, Adi; Onrizal, Onrizal; Andriansyah, M.; Muslim, Teguh (Indonesian Journal of Forestry Research, 2018)
To date, performance of the management of Indonesian production forests are discouraging. The concession areas, timber production and employment have been decreasing over time. concern on these matter and to improve management, a research was conducted for six years (2008-2013) and resulted in recommendations to implement the Multi-System of Silviculture (MSS) systems. Two products were generated in MSS; criteria and indicator to guide the selection of appropriate silvicultural system and supersilvik, a model to develop the best business plans. This paper evaluates and strengthens the recommendations through the simulation of MSS products in PT. Sarmiento Parakantja Timber (Sarpatim), Central Kalimantan, Indonesia. Various data variables were used, such as thematic maps of forest areas, data of stand, materials, equipments, labors, finances and incomes. Data were processed in a variety of formulations which were connected to each other in model systems to produce a variety of outcomes, such as production, finance, employment and tax contributions. Results offer four options to improve PT. Sarpatim performance, one of which is the best choice. Compared to the former business model under limited silvicultural systems, MSS projected an increase in the use of land, timber production and employment by 151-753%. Implementing MSS will provide a better and healthier finance for company with an increase of NPV up to 193%; as well as for government tax revenues with an increase up to 308%.